2014
DOI: 10.9724/kfcs.2014.30.2.193
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Supplementation of Zeolite on the Quality of Pork Shoulder Before and After Cooking

Abstract: The purpose of the study was to investigate the quality characteristics and sensory properties of fresh and boiling pork shoulder at different feed ration of zeolite (0, 0.5, 1.0 and 2.0%). All of the dietary zeolite groups had significantly higher pH than the control; 0.5% zeolite (6.14) had the highest pH. Cooking loss was significantly higher in the control compared to other treatments; further, the loss, increased as the feed ratio of zeolite addition increased. The cooking loss of fresh pork shoulder fed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Based on the nowadays knowledge, the production and consumption of rabbit meat in the world are negligible in comparison to other types of meat and thus also scientific work is more focused on poultry, pork, beef and poultry. The research of the effect of the zeolite (clinoptilolite) on the meat quality was already reported in chickens (Mallek et al, 2012), turkeys (Hcini et al, 2018), gees (Larina et al, 2020), pigs (Kim et al, 2014), and fish (Paritova et al, 2013). However, studies employing rabbit model for the zeolite administration focused only on the growth performance (Beshkenadze et al, 2016) or the effect on the thawed spermatozoa (Mohammed et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the nowadays knowledge, the production and consumption of rabbit meat in the world are negligible in comparison to other types of meat and thus also scientific work is more focused on poultry, pork, beef and poultry. The research of the effect of the zeolite (clinoptilolite) on the meat quality was already reported in chickens (Mallek et al, 2012), turkeys (Hcini et al, 2018), gees (Larina et al, 2020), pigs (Kim et al, 2014), and fish (Paritova et al, 2013). However, studies employing rabbit model for the zeolite administration focused only on the growth performance (Beshkenadze et al, 2016) or the effect on the thawed spermatozoa (Mohammed et al, 2019).…”
Section: Introductionmentioning
confidence: 99%